Si:
m= (2, -1, 3)
v= (0, 1, 7)
w= (1, 4, 5)
a) m x (v x w)
v x w = ((1) (5)-(7)(4)) i - ((0)(5)) - (1)(7)) j + ((0)(4) - (1)(1)) k=
v x w = -23 i + 7 j - 1 k
m x (v x w) = ((-1)(-1) - (7)(3)) i - ((2)(-1) - (-23)(3)) j + ((0)(7) - (-23)(-1)) k
m x (v x w) = 20 i - 6+7 j - 9 k
= - 56
b) (m x v) x w
m x v = ((-1)(7) - (1)(3)) i - ((2)(7) - (0)(3)) j + ((2)(1) - (0)(1)) k =
m x v = - 10 i - 14 j + 2 k
(m x v) x w = ((-4)(5) - (4)(2)) i - ((-10)(5) - (1)(2)) j + ((-10)(4= - (1)(-9)) k
(m x v) x w = - 28 i +52 j -36 k
= - 12
c) (m x v) - 2 w
= ((-4)(-10) - (-8)(2)) i - ((-10)(-10) - (2)(2)) j + ((-10)(-8) - (-2)(-4))
= 56 i - 104 j + 72 k
= 24
martes, 2 de septiembre de 2008
Suscribirse a:
Enviar comentarios (Atom)
No hay comentarios:
Publicar un comentario